Bone regeneration induced by a 3D architectured hydrogel in a rat critical-size calvarial defect. (January 2017) - Lohmann, P.; Willuweit, A.; Neffe, A.T.; Geisler, S.; Gebauer, T.P.; Beer, S.; Coenen, H.H.; Fischer, H.; Hermanns-Sachweh, B.; Lendlein, A.; Shah, N.J.; Kiessling, F.; et al.
Abstract: Bone regeneration can be stimulated by implantation of biomaterials, which is especially important for larger bone defects. Here, healing potency of the porous ArcGel was evaluated in a critical-size calvarial bone defect in rats in comparison with clinical standard autologous bone and Bio-Oss ® Collagen (BioOss), a bone graft material frequently used in clinics. Bone healing and metabolic processes involved were monitored longitudinally by [ 18 F]-fluoride and [ 18 F]-FDG μ-PET/CT 1d, 3d, 3w, 6w, and 12w post implantation. Differences in quality of bone healing were assessed by ex vivo μ-CT, mechanical tests and histomorphometry. The amount of bone formed after implantation of ArcGel was comparable to autologous bone and superior to BioOss (histomorphometry). Furthermore, microarchitecture of newly formed bone was more physiological and better functional in case of ArcGel (push-out tests). [ 18 F]-FDG uptake increased until 3d after implantation, and decreased until 12w for both ArcGel and BioOss. [ 18 F]-fluoride uptake increased until 3w post implantation for all materials, but persisted significantly longer at higher levels for BioOss, which indicates a prolonged remodelling phase. The study demonstrates the potential of ArcGel to induce restitutio ad integrum comparable with clinical standard autologous bone and better bone regeneration in large defects compared to a commercial state-of-the-art biomaterial.